UJI FAKTOR-FAKTOR YANG MEMPENGARUHI PENGEMBANGAN PENGUNGKAPAN MELALUI PRAKTIK PELAPORAN KEUANGAN BERBASIS INTERNET (INTERNET FINANCIAL REPORTING) (Studi Empiris Pada 100 Perusahaan Terkemuka di Indonesia) - Raihanil Jannah; Emrinaldi Nur DP; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examines the influence factors of the extent of disclosure through the internet-based financial reporting practices. In this research using the extent of disclosure through the internet-based financial practices as dependent variable. Independent variables are age, growth, public ownership, complexity of business, asset-in-place, and company based. The population of this research is a company registered in Indonesia Stock Exchange. While the study sample is a company registered in Indonesia Stock Exchange and in the category of Kompas-100 Index. Data analysis method used to perform hypothesis testing is multiple regression analysis. Hypothesis testing using analysis regression showed that variables public ownership, complexity of business, asset-in-place, and company based can influence the extent of disclosure through IFR practices. While age, and growth of company can’t influence the extent of disclosure through IFR practices.Keywords: IFR, Age, Growth, and Ownership